Overcoming CAP with Consistent Soft-State Replication. - Birman, Kenneth; Freedman, Daniel; Huang, Qi; Dowell, Patrick (Computer (00189162), 2012)
New data-consistency models make it possible for cloud computing developers to replicate soft state without encountering the limitations associated with the CAP theorem.